2023
DOI: 10.1088/1361-6528/acedb4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of variable thermal conductivity on flow of trihybrid nanofluid over a stretching surface

Saeed Ullah Jan,
Umar Khan,
Saeed Islam
et al.

Abstract: The present article describes the impact of variable thermal conductivity on the flow of ternary hybrid nanofluid with cylindrical shape nanoparticles over a stretching surface. Three nanoparticles combine in base fluid polymer. The assumption made will be used to model an equations. Modeled equations are in the form of a system of partial differential equations are difficult to solve can be converted to system of an ordinary differential equations, through resemblance substitutions, and will be solved numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…With the significance of the variable magnetic field, the properties of the micropolar fluid on distinct mediums were explored by Nadeem et al 14 Through a stretched, slender medium, the thermal analysis and flow mechanism based on magnetic properties in a fluid containing distinct nanoparticles were addressed by Elsebaee et al 15 Recent studies on the magnetized flow of hybrid nanofluids can be found in ref. 16–24.…”
Section: Introductionmentioning
confidence: 99%
“…With the significance of the variable magnetic field, the properties of the micropolar fluid on distinct mediums were explored by Nadeem et al 14 Through a stretched, slender medium, the thermal analysis and flow mechanism based on magnetic properties in a fluid containing distinct nanoparticles were addressed by Elsebaee et al 15 Recent studies on the magnetized flow of hybrid nanofluids can be found in ref. 16–24.…”
Section: Introductionmentioning
confidence: 99%